Aspects of Neurodevelopment Between Autism Spectrum Disorders and Epilepsy - Carvajal-Game, M (ACAD MEXICANA NEUROLOGIA, 2022)
There are high incidences of epilepsy and autism in the preschool and school ages. in which the synaptic plasticity and synaptogenesis are more active, a primary interruption of the synaptic function due to injury or genetic mutation may result in the appearance of both pathologies as in Lennox Gastaut S., De Aircadi S, epilepsy with continuous slow waves during sleep and Landau Kleffner S. There is evidence of abnormal brain maturation in autism spectrum disorders (ASD). Normal pruning eliminates faulty connections and optimizes neuronal functioning. In autism, this pruning would result in degrees of anatomical "over-connectivity" that increases or decreases the efficiency of communication between cortical regions. The same occurs with axonal myelination that affects integrated interregional cortical communication and synchronization. Critical and vulnerable mechanisms are appreciated during the peri-neonatal period, with subsequent stabilization of the synapses to form pre-designed neural networks through genetic mechanisms and modified by environmental factors. There are anomalies in different proteins that modulate the first phase of synaptogenesis, mutations in protocadherins, cadherins, and abnormalities in glutamatergic and GABAergic systems that affect the brain. All these aspects are critical for learning, language, and memory in both autism and epilepsy.